MiRNAs in malignant melanoma - Mione, Maria; Liebig, Janika; Munoz, Leonel; Boßerhoff, Anja Katrin (Springer International Publishing, 2017)
MicroRNAs (miRNAs) represent a class of small noncoding RNAs, first described in the nematode Caenorhabditis elegans. In 1993, the labs of Victor Ambros (Lee et al. Cell 75:843-854, 1993) and Gary Ruvkun (Wightman et al. Cell 75:855-862, 1993) discovered lin-4, the first member of the inexorably growing family of miRNAs. Interestingly, it was not until the year 2000 that Reinhart and colleagues detected a second miRNA species-let-7 (Reinhart et al. Nature 2000;403:901-906). The finding that the sequence of let-7 was conserved in a large variety of Metazoens from Drosophila to humans (in contrast to lin-4, which is exclusively expressed in Caenorhabditis; Pasquinelli et al. Nature 408:86-89, 2000; Slack et al. Mol Cell 2000;5:659-669, 2000) fueled miRNA research and revealed that this class of molecules is involved in the regulation of gene expression at a posttranscriptional level in presumably every multicellular organism. To date, more than 1800 distinct miRNA species have been identified in the human genome (www.miRNA.org Kozomara and Griffiths-Jones 42(Database issue):D68-73, 2014). Those are estimated to regulate the expression of as much as 60 % of all human transcripts (Friedman et al. Genome Res 2009;19:92-105, 2009). MiRNAs are demonstrably involved in the physiological regulation of multiple cellular processes, such as proliferation, apoptosis, and differentiation. As a consequence, abnormalities in miRNA activity were found to contribute to the pathogenesis and progression of various types of human cancers (reviewed by Mirnezami et al. Eur J Surg Oncol 35:339-347, 2009; Visone and Croce Am J Pathol 2009;174:1131-1138, 2009), including malignant melanoma (reviewed by Mione and Bosserhoff Pigment Cell Melanoma Res 2015;28:340-354).
CRIS-Team Scopus Importer:2022-08-05